2014
DOI: 10.1002/2014gc005242
|View full text |Cite
|
Sign up to set email alerts
|

A novel framework for quantifying past methane recycling by Sphagnum‐methanotroph symbiosis using carbon and hydrogen isotope ratios of leaf wax biomarkers

Abstract: The concentration of atmospheric methane is strongly linked to variations in Earth's climate.Currently, we can directly reconstruct the total atmospheric concentration of methane, but not individual terms of the methane cycle. Northern wetlands, dominated by Sphagnum, are an important contributor of atmospheric methane, and we seek to understand the methane cycle in these systems. We present a novel method for quantifying the proportion of carbon Sphagnum assimilates from its methanotrophic symbionts using sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…4). In general, methane oxidation producing 13 C-depleted CO2 mostly happens in aerobic peat and inside Sphagnum cells [44], thus the signal of 13 C-depleted CH4 (δ 13 C -94 --38 ‰) [45] can be returned to the same peat column as plant biomass or as microbial biomass. Besides 410 methane oxidation, a plausible explanation for surface and basal peat δ 13 C correlation may be the continuous return of CO2 from peat respiration back to vegetation through photosynthesis, thus refixation of CO2 released from the same vertical location.…”
Section: Discussionmentioning
confidence: 99%
“…4). In general, methane oxidation producing 13 C-depleted CO2 mostly happens in aerobic peat and inside Sphagnum cells [44], thus the signal of 13 C-depleted CH4 (δ 13 C -94 --38 ‰) [45] can be returned to the same peat column as plant biomass or as microbial biomass. Besides 410 methane oxidation, a plausible explanation for surface and basal peat δ 13 C correlation may be the continuous return of CO2 from peat respiration back to vegetation through photosynthesis, thus refixation of CO2 released from the same vertical location.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen isotope ratios of individual n-alkanes were determined by continuous flow isotope ratio mass spectrometry. Eluent from a gas chromatograph (Thermo Trace GC) passes through a pyrolysis reactor (Thermo GC IsoLink) where organic compounds are converted to H 2 gas, which then is passed to the IRMS (Thermo Delta V) via a continuous flow device (Nichols et al, 2014a).…”
Section: Methodsmentioning
confidence: 99%
“…They showed 13 C-depleted values are related to low water table depths and vice versa. Furthermore, Nichols et al (2014) presented a novel method for quantifying of carbon Sphagnum assimilates symbionts using stable isotope ratios of leaf-wax biomarkers. They indicated that carbon ratios of Sphagnum compounds are determined by water content and the isotope ratios of source carbon competing influences.…”
Section: Introductionmentioning
confidence: 99%